Faktor Pembentuk Adopsi Keuangan Digital dan Pengaruhnya Terhadap Kinerja UMKM - Worokinasih, Saparila; Normawati, Rani Arifah; Imamah, Nur; Rahimah, Anni (Seminar Nasional Manajemen, 2024)
This study explores how cyber security awareness impacts cyber security preparedness and the adoption of digital finance, drawing on the Hierarchy of Effects Model. Additionally, it assesses how cyber security preparedness and digital finance adoption influence the performance of SMEs, based on the Resources-Based Theory. The research is centered on SMEs in Indonesia, involving 185 SMEs. Data collection was carried out through surveys, and the analysis utilized SEM-PLS. The findings from the influence test reveal that cyber security awareness and cyber security preparedness have a significant effect on digital finance adoption. Surprisingly, cyber security awareness dominates digital finance adoption, with a path coefficient of 0.576. The implications derived from this study emphasize the importance of initiatives aimed at improving awareness and comprehension of cyber security, as they play a crucial role in motivating SMEs to embrace digital financial technologies. Moreover, the adoption of digital finance emerges as a critical factor influencing SME performance, positioning digital finance as a catalyst for the growth of SMEs.